An Integrated IPMS–MAFMA Framework for Improving the Operational Efficiency of Clean Water Distribution Pump Systems - Ni Luh Putu Hariastuti; Muhammad Irfan (Jurnal Teknologi dan Manajemen, 2026)
PT. XYZ is a local government-owned company responsible for providing clean water services to the residents of Surabaya. To ensure reliable water distribution, the company must maintain high operational performance of its distribution pump system. However, operational activities are frequently disrupted by equipment failures and inadequate maintenance practices, resulting in reduced efficiency and service reliability. This study aims to improve operational performance and minimize machine failures by integrating the Integrated Performance Measurement System (IPMS) and Multi-Attribute Failure Mode Analysis (MAFMA) at the Central Distribution Pump House. The IPMS method was employed to identify and prioritize Key Performance Indicators (KPIs) requiring performance improvement based on their relative weights. Subsequently, the MAFMA method was applied to identify potential failure modes, evaluate associated risks, and determine appropriate corrective actions. The results indicate that KPI 9, namely the completion of non-routine maintenance work, obtained the highest priority weight of 0.174, indicating that it should be the primary focus for performance improvement. Furthermore, the MAFMA analysis identified a damaged foot valve as the most critical failure mode, with the highest Risk Priority Number (RPN) of 168. Based on these findings, the proposed improvements include developing contingency plans to manage unexpected priority changes and implementing routine inspection and cleaning of pump components every two days to reduce the likelihood of equipment failure. The integration of IPMS and MAFMA provides a systematic approach for enhancing maintenance performance, improving operational reliability, and supporting sustainable clean water services.